Cost of trans-boundary haze externalities - JAMAL OTHMAN,; MOHD SHAHWAHID H. O., (Penerbit Universiti Kebangsaan Malaysia, 1999)
This paper attempts to assess the economic value of the trans-boundary 1997 haze damages on health in Malaysia. Valuing the damage will help policy makers appreciate the scale of the problem as the values can be readily compared with other losses or the merits of alternative resource use. It also facilitates the establishment of common cross-country enviromental policy framework, which will benefit the affected region as a whole. The impacts on health are especially highlighted in this paper, as there is sufficient market data for the employment of appropriate secondary valuation technique, namely the Dose-Response Function. Policy implications, based on the findings of the study are offered. This study contributes substantially to the literature on environmentalvaluation in Malaysia. The Dose-Response Function would not be made possible without the given haze episode, where all relevant health data and pollution level were collected nationwide and on a daily basis. The Malaysian Dose-Response coefficient may also be transferred to other similar studies via a Benefit Transfer Protocol